Descriptive Study of the Use of Adjectives in the Novel Over The Moon by Soraya Nasution - Iskandar, Ramadhan Attalarik; Y. Yuliany; Pepen Priyawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Adjectives or better known as adjectives are one of the types of words in Indonesian. Adjectives are often paired with various other types of words such as verbs, nouns, adverbs, and so on. In this article the author discusses the words pure adjective, clitic, with the same prefix, with the most prefix, with the prefix –an, with the suffix –kan, with the same suffix, with the same confix, with the me-kan clofix, with the me-i clofix, the adjective word from the reduplication of the root word, the adjective word with the meaning component (+action), and the adjective word with the “absorption affix”. The author uses descriptive methodology or methods in the process of analyzing adjective words contained in the novel Over The Moon by Soraya Nasution. The research object in this research is the novel Over the Moon by Soraya Nasution. The results obtained in this research are that the word adjective in the novel Over The Moon consists of 229 adjective words, one of which is a pure adjective word consisting of 205 words with example sentences “Beautiful, intelligent, has a balanced family background with me, and presentable as long as you try to be better.” (OTM:H10:P91:K2). The conclusion of this research is that adjectives include adjectives which are part of word types, which include: pure adjectives, clitics, se-prefixes, ter-prefixes, and so on.